Walking and Quadriceps Isometric Exercises on Pain and Range of Motion in Osteoarthritis Patients - Matrahman, Matrahman (Health Gate, 2023)
Pain is known as the main symptom of Osteoarthritis (OA) which affect on the functional impairment and patient’s quality of life. Alternatively, isometric quadriceps exercise and walking exercise could be employed to reduce the pain among knee OA patients. This study aimed to identify the comparison between walking exercise and isometric quadriceps exercise on pain and joint range of motion in knee osteoarthritis patients. This research was used quasi-experimental with non equivalent control group before–after design. The experimental and control group, involved 17respondents respectively with consecutive sampling technique. The results showed the walking exercise is significantly reduce pain and increase knee flexion range of motion (p 0.000). Similarly, the isometric quadriceps exercise is significantly decrease pain and increase knee flexion range of motion (p 0.000). Nevertheless, after being compared showed that walking exercise is no more effective reduce pain and increase knee flexion range of motion rather than isometric quadriceps exercise in knee osteoarthritis patients. A standard operational procedure for walking exercise and isometric quadriceps exercise is programmed.